Estudio de prefactibilidad para la instalación de un complejo temático de salas de escape - Prado Galindo, Martha Sofia (2022)
The objective of this project is to be able to validate the economic, technical and financial viability of an escape room complex in a shopping center in Metropolitan Lima, for which research, design and evaluation tools will be used. The first and second chapters are made up of the analysis of the micro and macro environment. A market study was carried out to calculate the demand for the project, which is represented by 35 313 visits in the first year, culminating in 37,608 visits at the end of the project. In the third chapter, according to the macro and micro location criteria, the chosen place was the Jockey Plaza shopping center in the city of Lima Metropolitana. In the fourth chapter, the capacity of the service was calculated in which the market sizes, investment, resources, technology, investment, equilibrium point, service dimension were analyzed and the size - market was identified as the main limiting factor. In the fifth chapter, it was found that 80 m2 are necessary to satisfy the demand. For the construction of escape rooms, there will be design providers and for the execution of the plans, general service providers will be hired. Customer service, maintenance and security protocols were defined. In the sixth chapter, the type of SAC company was defined, and the number of administrative workers was established, followed by the organizational structure. In the seventh chapter, the profitability of the project was calculated, obtaining a financial VAN of 550 834 and a financial TIR of 183%, demonstrating the viability of this project. In addition, a benefit-cost ratio of 6.43 and a payback period of 0.64 years were obtained. In the eighth chapter, the calculation of the added value of this project will be observed, which was S/ 3 197 142 Finally, the conclusions of the present investigation and the necessary recommendations for the correct execution of the project were made.